Tax Strategies And Compliance In South-West Nigeria - Olumoh, Yusuf Alabi; Sanni, Mubaraq; Mustapha, Abdulrasaq; Abdulrasheed, Abdullahi Taiwo; Oluwole, Shuaib Abdul-Hakeem; Sanni, Mubarak Olayiwola; Ibrahim, Salaudeen (Universitas Indonesia Membangun (Inaba), 2025)
Tax compliance remains a significant challenge in developing economies, where inadequate tax strategies and weak enforcement mechanisms hinder effective revenue generation and economic development. Given the issues, this study aims to examine the impact of tax strategies on tax compliance in South-West Nigeria. Specifically, the study seeks to: assess the effect of tax planning strategies on tax compliance, evaluate the influence of compliance and risk management strategies on tax compliance, investigate the impact of tax avoidance strategies on tax compliance, and determine the moderating effect of regulatory enforcement on the relationship between tax strategies and tax compliance in South-West Nigeria. A cross-sectional survey design was adopted, targeting a population of 159,000 taxpayers and 8,818 SIRS staff with a sample size of 399 and 383 respondents. Data was analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to establish relationships among the study variables. The findings reveal that tax planning and compliance and risk management strategies positively influence tax compliance, while tax avoidance strategies negatively impact compliance. The study concludes that effective tax planning and robust compliance measures can enhance adherence to tax regulations, with regulatory enforcement playing a crucial role in strengthening compliance efforts. It recommends that tax authorities in South-West Nigeria implement stronger regulatory frameworks, improve taxpayer education, and leverage digital tools to monitor and mitigate tax avoidance practices, thereby fostering a more compliant tax environment.